Purpose in Thermodynamics - Adrian Bejan; George Tsatsaronis (Energies, 2021)
This is a review of the concepts of purpose, direction, and objective in the discipline of thermodynamics, which is a pillar of physics, natural sciences, life science, and engineering science. Reviewed is the relentless evolution of this discipline toward accounting for evolutionary design with direction, and for establishing the concept of purpose in methodologies of modeling, analysis, teaching, and design optimization. Evolution is change after change toward flow access, with direction in time, and purpose. Evolution does not have an ‘end’. In thermodynamics, purpose is already the defining feature of methods that have emerged to guide and facilitate the generation, distribution, and use of motive power, heating, and cooling: thermodynamic optimization, exergy-based methods (i.e., exergetic, exergoeconomic, and exergoenvironmental analysis), entropy generation minimization, extended exergy, environomics, thermoecology, finite time thermodynamics, pinch analysis, animal design, geophysical flow design, and constructal law. What distinguishes these approaches are the purpose and the performance evaluation used in each method.